Bioecological assessment of the state of the adventitious fraction of the dendroflora of recreational and park landscapes (Dnipro) - Shamray, Marina; Didur, Oleh (Видавництво Львівської політехніки, 2022)
The state of seed self-regeneration of woody plants of Kyrylivka Park (Dnipro, Ukraine) in areas with a strong, moderate and non-existent level of recreational load was studied. Floristic methods (estimates of species richness, determination of floristic community and homogeneity), methods of ecological analysis of vegetation, physico-chemical methods of soil analysis, statistical methods are applied. It was established for the first time that in Kyrylivka Park, artificial stands are capable of forming a sufficient amount of viable undergrowth of autochthonous (53.5 %) and introduced (46.5 %) species. The amount of tree growth of adventitious plants in the areas according to the level of recreational load is distributed as follows: with no load – 32.2 % of the number of self-regenerating trees, with moderate – 41.3 %, with strong – 89.7 %. The indices of species richness of Margalef and Menkhinik of self-regenerating tree species for the site with a strong recreational load turned out to be the largest (at the expense of adventitious species) compared to the sites with a moderate recreational load and without it. The calculated Koch index of biotic dispersion (40.0 %) indicates a certain process of floristic homogenization of the tree stand in the investigated territory of the park. The correlation coefficients between the number of self-restored allochthonous and autochthonous tree species for the studied areas with strong, moderate and absent recreational loads are significant (0.90, 0.92 and 0.88 respectively). The need to analyze and forecast the possible remote consequences of the introduction of alien species in the composition of the dendroflora is emphasized.
Keywords: autochthonous and alien species of plants; green zone of the city; tree plantations; seed self-regeneration